The unscripted image. (1st April 2015) - Talbot, Emma
The article compares and discusses Ken Loach and Mike Leigh's very different and distinct strategies for realist film-making. Loach's use of the script is compared to the use of photography in painting with reference to 'The Painting of Modern Life' exhibition at the Hayward Gallery (2007), and Mike Leigh's experimental, improvised and unscripted approach is compared to Carel Weight's painting The Friends (1968) that uses observation and experience.